2020
DOI: 10.1155/2020/5847429
|View full text |Cite
|
Sign up to set email alerts
|

Combined Administration of Bisphosphonates, Chemotherapeutic Agents, and/or Targeted Drugs Increases the Risk for Stage 3 Medication-Related Osteonecrosis of the Jaw: A 4-Year Retrospective Study

Abstract: Objectives. Patients with stage 3 medication-related osteonecrosis of the jaw (MRONJ) suffer from severe complications. Chemotherapeutic agents and targeted drugs are considered to be associated with the development of MRONJ. However, little is known regarding the association of those agents with stage 3 MRONJ. The purpose of this study is to analyze the comprehensive medication history of patients with advanced-stage MRONJ (stage 2 and stage 3) and evaluate the possible risk factors for stage 3 MRONJ. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Patients attributable to the three stages of the disease were treated, with a higher frequency of cases attributable to stage II. It has been reported that early stage treated with radical surgery showed a better treatment outcome [50]. Nevertheless, the MRONJ stage did not play a significant role in the incidence of surgical failure (p = 0.2352), in this case series.…”
Section: Discussioncontrasting
confidence: 49%
“…Patients attributable to the three stages of the disease were treated, with a higher frequency of cases attributable to stage II. It has been reported that early stage treated with radical surgery showed a better treatment outcome [50]. Nevertheless, the MRONJ stage did not play a significant role in the incidence of surgical failure (p = 0.2352), in this case series.…”
Section: Discussioncontrasting
confidence: 49%
“…In addition to well-known medications, MRONJ may be a major adverse reaction to several new-generation anticancer drugs due to unknown mechanisms [ 57 , 58 ]. To date, several medications have been somehow implicated in MRONJ on the basis of experience gained through isolated data, case series reports, and literature reviews [ 16 , 17 , 18 , 59 , 60 ]. Recent reports have suggested a relatively high MRONJ risk in patients with a combined administration of bisphosphonates and targeted drugs [ 30 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested a relatively high MRONJ risk in patients with a combined administration of bisphosphonates and targeted drugs [ 30 , 49 ]. It is known, for example, that the combination of anti-VEGFR and bone antiresorptive agents may increase the risk of MRONJ [ 60 , 61 , 62 ]. Similarly, it was well confirmed that mTOR inhibitors have a strong immunosuppressive effect, which can lead to delayed healing of oral soft tissues and persistent infections favoring the onset of the osteonecrotic process [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exposure to these drugs is a major risk factor for the development of MRONJ. Recent data suggest that combination therapies might also increase the risk of developing MRONJ and cause more advanced necrosis especially in the maxilla; however, this study was not limited to patients with myeloma [22]. Another study of 459 MRONJ cases reported that out of 52 patients undergoing treatment with BMA, 11 had also received lenalidomide, 12 received thalidomide, 11 received bevacizumab, 9 received everolimus, and 9 received sunitinib as part of the drug therapy [2].…”
Section: Medicationsmentioning
confidence: 99%